2011
DOI: 10.1108/00070701111174578
|View full text |Cite
|
Sign up to set email alerts
|

ACE inhibitory activity and bioconversion of isoflavones by Lactobacillus in soymilk supplemented with B‐vitamins

Abstract: PurposeThe aim of this study is to examine the bioactive properties of lactobacilli‐fermented B‐vitamin soymilk, namely the in‐vitro antihypertensive property and bioconversion of isoflavone glucosides to aglycones.Design/methodology/approachLactobacillus acidophilus BT 1088, L. fermentum BT 8219, L. acidophilus FTDC 8633 and L. gasseri FTDC 8131 were investigated for their bioactive potential and enhanced bioconversion of isoflavones in soymilk supplemented with individual B‐vitamins at a concentration of 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Soymilk fermented by UVB treated lactobacilli has also been found to contain significantly lower (P < 0.05) concentration of malonyl-and b-glucosides compared to that of the control and other UV radiation studied. This was attributed to higher doses of UVB treatment on lactobacilli that had led to enhance b-glucosidase enzyme and cleavage of b-1,6-glucosidic linkage to release bioactive aglycones during the fermentation of soymilk (Ewe et al, 2011).…”
Section: Concentrations Of Isoflavone Glucosides and Aglycones In Biomentioning
confidence: 99%
See 3 more Smart Citations
“…Soymilk fermented by UVB treated lactobacilli has also been found to contain significantly lower (P < 0.05) concentration of malonyl-and b-glucosides compared to that of the control and other UV radiation studied. This was attributed to higher doses of UVB treatment on lactobacilli that had led to enhance b-glucosidase enzyme and cleavage of b-1,6-glucosidic linkage to release bioactive aglycones during the fermentation of soymilk (Ewe et al, 2011).…”
Section: Concentrations Of Isoflavone Glucosides and Aglycones In Biomentioning
confidence: 99%
“…The isoflavones from fermented soymilk was extracted and analyzed according to the method of Ewe et al (2011). Concentrations of isoflavones were determined using high performance liquid chromatography (HPLC).…”
Section: Evaluation Of Bioconversion Of Isoflavones In Soymilkmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that the β-glucosidases possessing intestinal microbiota, such as lactobacilli, are involved with the hydrolysis of glucose moiety from glucoseconjugated isoflavones, producing aglycone configurations that are more bioavailable and biologically active [44]. The fermentation of soymilk with β-glucosidases-possessing lactobacilli has been reported to contain higher amounts of aglycones than glucosides conjugates of isoflavones [12].…”
mentioning
confidence: 99%